The Relationship Between Learning Facilities And Learning Interest In Fashion Design Mode Program At Community Reading Center - Zerli Fradila; Vevi Sunarti (Universitas Negeri Padang, 2022)
Non-formal education is intended for people who specifically need education as a complement, addition to, and substitute for formal education. Non-formal education can be used as a support, a complement, an addition to the education obtained by a person in formal education, where non-formal education is held for people who need this education. Non-formal education includes equality education, training and work skills, functional literacy, women's empowerment, youth, PAUD, life skills, and others.Community Reading Park (TBM) is one of the institutions in the field of non-formal education. Community reading parks can be interpreted as non-formal educational institutions that focus on providing knowledge services in the form of print media (books) or electronic media (internet). On the other hand, the community reading park also functions as a supporter of non-formal education activities, one of which is literacy education.Fashion design is a non-formal education program that focuses on the science of designing and sewing clothes. This program is implemented in various non-formal educational institutions, one of which is the Community Reading Center (TBM). There is an important component in the fashion design program, namely facilities for learning. Learning facilities are said to be an important component because they are able to encourage a person's interest in participating in a learning program. Interest in learning is an element in supporting the success of the learning program. Without high interest from program participants, it will create failure in a program. Facilities have a relationship with interest in learning in achieving a successful program. Keywords: TBM and non-formal education